Gender role stereotypes in elementary school textbooks (Edukasyon, 1995)
The stories and pictures in elementary school textbooks were content analyzed to determine male and female role stereotypes. Reading and Language textbooks in both English and Filipino were analyzed using the categories of family, occupation and activity. It was found that male and female roles differ. Females are more often portrayed in the home doing a variety of domestic work. The proportion of female codes in the family category exceeds that of males in both stories and pictures in textbooks in English and in Filipino. Males have a dominant role in the occupation category. This is shown in the proportion of male occupation roles which is greater than that for females. Moreover, the male occupational roles take a wide range, a stark contrast with the very limited occupational roles of females. This is evident in stories and pictures in textbooks in English as well as in Filipino. In the activity category, females are shown engaged in domestic activities such as cooking food and washing clothes whereas males are engaged in sports or occupation-related activities. Gender stratification theories are suggested to complement social learning and cognitive-developmental theories in explaining gender role stereotypes. Recommendations for the revision of stories in elementary school textbooks include depicting a wider range of roles of females in the public sphere and for males in the domestic sphere and reflecting the richness in cultural composition of Philippine society. Further research on gender analysis of content of textbooks should employ a relational framework.